THE EFFECT OF THE BANDUNG EMERGENCY APPLICATION SUPPORT (BEAS) ON RESPONSE TO EMERGENCY VICTIMS BY THE PUBLIC SAFETY CENTER (PSC) 119 - Abdul Aziz; Ayu Rizki Prabaningtyas; Sri Gunarni; Suciani Nurlestari; Davina Azzahrawaani Salsabila (CV. Fahr Publishing, 2026)
Delayed response to emergency victims remains a critical problem in pre-hospital care because it may affect patient safety. Bandung Emergency Application Support (BEAS) was developed to accelerate reporting, clarify incident locations, and support coordination within Public Safety Center (PSC) 119 in Bandung City. This study aimed to analyze the effect of BEAS on response time, triage accuracy, and initial patient outcomes. A quasi-experimental pretest-posttest design was applied to 714 PSC 119 operational records, consisting of 357 cases before and 357 cases after BEAS implementation. Response time was analyzed using an independent t-test, whereas triage accuracy and initial patient outcomes were analyzed using Pearson chi-square tests at a significance level of p<0.05. The mean response time decreased from 12.5 to 9.1 minutes (p<0.001). Triage accuracy increased from 72.0% to 88.0% (p<0.001), while the proportion of patients arriving alive at the hospital increased from 84.9% to 89.9% (p=0.042). These findings indicate that BEAS contributes to faster coordination, improved triage accuracy, and better early outcome indicators in emergency care. Strengthening an integrated digital system through operator training, standard operating procedures, and periodic evaluation is required to sustain the benefits of BEAS and support replication in other PSC 119 services.